Psychosocial Perceptions as Significant Impact Modifiers - A Mixed Method Research Among Hospitalized Covid-19 Patients in A Tertiary Care Hospital in Coimbatore District, Tamil Nadu - Punithakumari Purushothaman; Susila T; Iswarya Santhanakrishnan; Saranya Rajamanickam; Karthikeyan K; Babu Samuel (Medsci Publications, 2022)
Context: Covid 19 pandemic which evolved in successive waves had profound pyschosocial impact on affected individuals. Perceptions had impact on both individual and environmental level with potential behavioural consequences. The aim of the research is to study the psychosocial perception and psychological impact of COVID- 19 among hospitalized COVID-19 patients. Methodology: The study was a mixed method research (Quan-Qual sequential design) conducted in the Covid wards of a tertiary care hospital in Coimbatore district. The psychological impact was assessed using the General Health Questionnaire, Perceived Stress Scale. The results of quantitative analyses and qualitative analyses were expressed as proportions and done using thematic analysis using grounded theory respectively. Results: About 55% of the hospitalized Covid-19 patients had psychological impact. On multivariate analysis, the factors which emerged as independent risk factors for presence of psychological morbidities due to COVID were presence of high stress level, sleep disturbances and their perception of COVID as high threat. Conclusions: Focussed Counselling with specific reference to attend to spiritual health component in addition, would go a long way in diminishing immediate and long-term psychological impact due to covid-19 illness.